The effectiveness of reflexology on blood pressure in pregnant women - AS, Emilda; Asmanidar, Asmanidar (Institute of Computer Science (IOCS), 2025)
High blood pressure during pregnancy, such as gestational hypertension and preeclampsia, is a serious complication that can pose risks to both the mother and fetus. Foot reflexology has emerged as a promising non-pharmacological intervention to help manage blood pressure. This study aimed to systematically review the effectiveness of reflexology therapy in reducing blood pressure among pregnant women. A systematic review was conducted using 18 scientific articles published between 2013 and 2024, retrieved from Google Scholar and PubMed databases. The selected articles included both quantitative and qualitative studies focusing on the use of reflexology as an intervention for managing blood pressure during pregnancy. The data analyzed covered research design, sample size, intervention protocols, and blood pressure outcomes. The findings indicate that foot reflexology consistently reduces both systolic and diastolic blood pressure, especially in pregnant women with gestational hypertension. The mechanism of reflexology involves stimulating specific reflex points related to the cardiovascular and endocrine systems, as well as activating the parasympathetic nervous system to promote relaxation and stress reduction. Reflexology has also been shown to be safe, as it does not induce uterine contractions, and can be effectively combined with other non-pharmacological therapies such as warm foot soaks and aromatherapy for optimal results. Although further research with stronger study designs is needed, current evidence supports the use of reflexology as a complementary therapy in managing blood pressure during pregnancy.